2016
DOI: 10.1371/journal.pone.0149557
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 Levels Are Decreased in the Cerebellum of Multiple-System Atrophy Patients

Abstract: BackgroundThe objective of this study was to evaluate whether the levels of coenzyme Q10 (CoQ10) in brain tissue of multiple system atrophy (MSA) patients differ from those in elderly controls and in patients with other neurodegenerative diseases.MethodsFlash frozen brain tissue of a series of 20 pathologically confirmed MSA patients [9 olivopontocerebellar atrophy (OPCA) type, 6 striatonigral degeneration (SND) type, and 5 mixed type] was used for this study. Elderly controls (n = 37) as well as idiopathic Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
45
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 22 publications
7
45
2
Order By: Relevance
“…The pathogenesis of MSA remains an enigma, though it is becoming clear that genetic associations exist. Many mechanisms for the development and propagation of MSA have been postulated, including impaired elimination of α-synuclein within the cell, [41][42][43][44] mitochondrial dysfunction, 32,33,45,46 direct toxicity of α-synuclein, 47 oxidative stress, 48 and neuroinflammation. 49,50 More recently, there are also data that implicate a prion-like propagation of MSA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenesis of MSA remains an enigma, though it is becoming clear that genetic associations exist. Many mechanisms for the development and propagation of MSA have been postulated, including impaired elimination of α-synuclein within the cell, [41][42][43][44] mitochondrial dysfunction, 32,33,45,46 direct toxicity of α-synuclein, 47 oxidative stress, 48 and neuroinflammation. 49,50 More recently, there are also data that implicate a prion-like propagation of MSA.…”
Section: Resultsmentioning
confidence: 99%
“…[26][27][28][29][30][31] Further studies have revealed reduction in CoQ10 levels in the cerebellum and serum of patients with MSA. 32,33 These findings may be particularly important in implicating CoQ10 supplementation as a therapeutic option in MSA, though this has not yet been systematically studied.…”
Section: Coenzyme Q2 Genementioning
confidence: 99%
“…9 Therefore, the rare patients with MSA and COQ2 mutations may be regarded as having an adult-onset variant of primary CoQ10 deficiency without prominent ophthalmologic or renal involvement. By contrast, individuals with sporadic MSA show a selective decrease of levels of CoQ10 in the cerebellum, 10,11 potentially owing to environmental, genetic or epigenetic, and other factors influencing CoQ10 biosynthetic pathways. A study of enzyme levels in the CoQ10 biosynthetic pathways revealed that levels of PDSS1 and COQ5, but not other CoQ10-synthesizing enzymes, are selectively decreased in the cerebellum of patients with MSA.…”
mentioning
confidence: 94%
“…1 These molecular findings have revealed the importance of the CoQ10 biosynthetic pathway in MSA and raise the question: is CoQ10 deficiency also present in the brains of patients with sporadic MSA because of a shared disease mechanism between genetic and sporadic MSA? To address this issue, Schottlaender et al 10 found that patients with sporadic MSA have decreased levels of CoQ10 in the cerebellum but normal levels in the frontal cortex when compared with controls. In addition, one study observed that patients with MSA without COQ2 mutations have 40% lower levels of CoQ10 in the cerebellum compared with controls, whereas the occipital cortex has normal levels of CoQ10.…”
mentioning
confidence: 99%
See 1 more Smart Citation